Pertautan yang Real dengan yang Rasional dalam Epistemologi Thomas Aquinas - Fransisca Y Sri Winarsih (Jurnal Orientasi Baru, 2015)
The discussion on the relationship between the real and the rational has been slanting the history of philosophy since the time of classical Greece to contemporary times. This article discusses Thomas Aquinas critical analytical thinking about the theme above. The aim of the reach of the research is to find out the thought of Thomas Aquinas synthesis of themes such as the enlightenment for enthusiasts philosophical thinking. Aquinas agreed with Platos position stating that the real world to participate world of ideas. According to Aquinas point of view, Plato and Aristotle are both correct and wrong. Yet, Thomas against Platos statement which said that concrete life separate from forma. In a confrontation with the thought of Aristotle, Thomas agreed that forma tied to the material. But he rejected Aristotles said that the forma has no relation to life eternal. Aquinas was a moderate realist who accepts the existence of a universal. The universal exists in the human mind, also in any content and at the same time there is transcendent in the mind of God.